The Positive Impact of International School Teacher Pedagogy in Managing the Behavior of Students from Different Cultures - Rosmiati; Tukiyo; Israkwaty (Universitas Pendidikan Ganesha, 2025)
The increasing cultural diversity in international schools poses challenges for teachers in managing student behavior effectively. The urgency of this research is the need for inclusive and culturally sensitive pedagogical strategies to create a harmonious learning environment. The purpose of this research is to analyze the relationship between cross-cultural communication competence, student behavior management strategies, the implementation of inclusive learning, and the effectiveness of multicultural classroom management. The research approach is mixed methods. The research sample consisted of 120 teachers from four international schools. Data collection techniques used a Likert scale questionnaire and in-depth interviews. Data analysis was carried out using descriptive statistics, Pearson correlation tests, multiple linear regression, ANOVA, and thematic analysis. The results showed a significant positive relationship between all variables, with a correlation value of 0.801 for inclusive learning, 0.782 for cross-cultural communication competence, and 0.756 for behavior management strategies. The determination value of 0.745 indicates that the three variables simultaneously explain 74.5% of the effectiveness of multicultural classroom management, where inclusive learning is the most dominant factor. Qualitative findings show an increase in discipline, empathy, and collaboration among students after teachers implemented a cross-cultural approach. The conclusion confirms that inclusive pedagogy strengthens a harmonious classroom climate. The implication is that cross-cultural training should be prioritized in teacher professional development in international schools.